PENGARUH KOMPETENSI INDIVIDU,DISIPLIN KERJA DAN PENGAWASAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS KOPERASI, UKM DAN PERDAGANGAN KABUPATEN BARRU - Muhayyar Sabir; Saban Echdar; Maryadi Maryadi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to analyze (1) the effect of individual competence, work discipline and partial supervision of employee work productivity, (2) the effect of individual competence, work discipline and supervision simultaneously on employee work productivity, (3) analyze which variable is the most dominant affect employee productivity. The sample of this study was 36 respondents of Barru Regency Cooperative, SME and Trade Service employees, using multiple linear regression analysis with the help of the SPSS program. The results of hypothesis testing show that (1) individual competence (X1) and supervision (X2) have a positive and partially significant effect on work productivity, with a tcount of 2.235> ttable 2.036; and tcount 2.126> ttable 2.0. Work discipline does not have a significant effect on work productivity with a tcount of 0.623 <ttable 2.036, (2) F test results indicate that individual competence, work discipline and supervision have a simultaneous effect on work productivity, this can be seen from the Fcount value of 11.391> Ftable 2.86. Determinant coefficient test results show that the influence of independent variables (individual competence, work discipline and supervision) on the dependent variable (work productivity) is only 51.6%, while the remaining 48.4% is influenced by other variables not examined, (3) Variables the most dominant individual competencies influence employee productivity